ASEAN community comes into being - New Sabah Times English, (KK) (New Sabah Times English (KK), 2016)
PUTRAJAYA: The ASEAN Community comes officially into being today, marking a milestone in the 10-member bloc's history, deepening integration of the region for the prosperity and well being of all.